Development and optimization of alloy composition for transition zone of bimetal slug (carbon high-alloy steel) - D. M. Kukuj; G. I. Kleshchenak; O. G. Kleshchenak (Литьë и металлургия)
There are given the investigations results of optimization of alloy chemistry for transition zone of bimetallic casts, consisted of steel 45 and steels of 5X3V3MFS, 3X2V8F type. This work is carried out using the simplex-checker method of the mathematical planning of the experiment.